Correlation Between Communication Anxiety and Student Participation in Problem-Based Learning at the Faculty of Medicine, Universitas Nusa Cendana - Rabbani, Fikrama Avicena; Folamauk, Conrad Liab; Dedy, Maria Agnes (Universitas Nusa Cendana, 2025)
Background : Learning in medical faculty which has a stressfull environment will have negative effects and one of them is communication anxiety within students. Anxiety risks having a negative impact on students’ academic records, one of them in the form of PBL (Problem Based Learning) which emphasizes on tutorial based disscussions. Goal : To identify the correlation between communication anxiety rates and students’ activities within PBL at Medical Faculty, Nusa Cendana University. Method : This research is a quantitative research with a cohort prospective approach done on Medical Faculty Nusa Cendana University students class of 2019 by collecting PRCA-24 quesioners and PBL scores. Samples are gathered utilizing the simple random sampling with 43 respondants whom fullfill inclusive and exclusive requirements. The research was analyzed univaria-tly, bivariate-ly chi-square method. Results: Research about the correlation between communication anxiety rates and student activeness in PBL obtained p-value = 0.092 (> ∝ = 0.05) and r = 0,249. This means that the communication anxiety rates does not always affect PBL activeness because there are still other factors that support each other, such as the adaptation process that affects students, facilitators and scenarios that affect activeness in PBL, and self-confidence that affects communication anxiety among students. Conclusion : There has not been found any correlation between communication anxiety rates and students’ activities within Problem Based Learning at Medical Faculty Nusa Cendana University